IMPLEMENTASI KEBIJAKAN PELAYANAN KESEHATAN REPRODUKSI REMAJA DI KOTA SEMARANG - Rina Anggraeni; R. Slamet Santoso (Journal of Public Policy and Management Review, 2016)
This research uses descriptive qualitative research method. This study will describe and analyze Implementation Adolescent Reproductive Health Services in Kota Semarang along with the critical success factors that influence it. This policy refers to Government Regulation No. 61 Year 2014 on Reproductive Health and Planning Guide, Formation and Development PKPR in Regency / City. Data collection techniques used through interviews, observation and documentation of information. The theory used is the theory of five precision of public policy implementation and implementation models belonging to Grindle. The results of this study indicate that, implementation of the Adolescent Reproductive Health Care Policy in Semarang still less than optimal. Indicators that it is still not include policy measures, public acceptance, changes desired, the details of the implementing actor, resource availability, and the participation of the target group. Suggestions for improvement are given is to hold a special queue for teenagers, provide policy dissemination to parents, reproductive health education from grade 6, make regulations regional level descriptors, provides a dedicated space for counseling, and training of peer counselors each year at the city level.